2021
DOI: 10.3390/cancers13195033
|View full text |Cite
|
Sign up to set email alerts
|

High-Fat Diet-Induced Obese Effects of Adipocyte-Specific CXCR2 Conditional Knockout in the Peritoneal Tumor Microenvironment of Ovarian Cancer

Abstract: Obesity contributes to ovarian cancer (OC) progression via tumorigenic chemokines. Adipocytes and OC cells highly express CXCR2, and its ligands CXCL1/8, respectively, indicating that the CXCL1/8-CXCR2 axis is a molecular link between obesity and OC. Here, we investigated how the adipocyte-specific CXCR2 conditional knockout (cKO) affected the peritoneal tumor microenvironment of OC in a high-fat diet (HFD)-induced obese mouse model. We first generated adipocyte-specific CXCR2 cKO in mice: adipose tissues were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 51 publications
(77 reference statements)
0
2
0
Order By: Relevance
“…In another in vivo study, it was observed that C57B6 mice fed with HED and CRD and treated daily with the anti-diabetic agent metformin displayed a significant reduction in tumor volume along with a reduction in circulating levels of IGF-1, IL-6, and leptin in both plasma and ascetic fluid, similar to the CRD mice [194]. Overall, in vivo investigations demonstrated the positive correlation between obesity and ovarian cancer [234,235], although some of those did not investigate circulating leptin levels.…”
mentioning
confidence: 84%
“…In another in vivo study, it was observed that C57B6 mice fed with HED and CRD and treated daily with the anti-diabetic agent metformin displayed a significant reduction in tumor volume along with a reduction in circulating levels of IGF-1, IL-6, and leptin in both plasma and ascetic fluid, similar to the CRD mice [194]. Overall, in vivo investigations demonstrated the positive correlation between obesity and ovarian cancer [234,235], although some of those did not investigate circulating leptin levels.…”
mentioning
confidence: 84%
“…CXCR2 is a chemokine secreted by adipocytes and has been associated with increased tumor burden in vivo compared to knock out animals, which had higher levels of ovarian cancer cells in ascites. CXCR2 is associated with obesity, a known risk factor for HGSOC ( 173 ) ( Figure 4A ).…”
Section: Microenvironment At Metastatic Nichesmentioning
confidence: 99%